Development of Risk Management Mitigation Plans for the Infant Formula Milk Supply Chain Using an AHP Model - Mona Haji (18526764) (2023)
Infant formula milk (IFM) is critical in the diet of many babies and must be of high-quality. Unfortunately, IFM has been a target of adulteration by those attempting to make illegal profits and has suffered from contamination-related issues. This study’s main objective was to identify the most critical risks affecting IFM quality in the supply chain and determine mitigation strategies to improve IFM performance measurement. We developed a model to reduce adulteration and contamination rates in the infant formula milk supply chains (IFMSCs) and maximize safety. The steps to achieve the study’s objectives included: (1) identifying the importance of IFMs for infant nutrition and their risks; (2) establishing mitigation criteria for evaluating IFMSC’s performance to maximize quality; and (3) analyzing each mitigation criterion to maximize IFM safety. Based on pairwise comparisons by professionals in the food supply chain (FSC) of decision-making, the Analytic Hierarchy Process (AHP) model was used to analyze and prioritize mitigation alternatives. According to the contamination quality risk agent, mitigation alternative (QR.M2) ranked highest. This study’s findings illustrate how vital avoiding risk is when dealing with public health, especially infants’ health, and how IFM must undergo precise testing and quality checks at every supply chain stage to ensure quality. Other Information Published in: Applied Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/app13137686